(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In today’s age of globalization and technology, protecting our youth from the negative effects of "mass culture" is one of the most responsible tasks before each of us. These issues have their theoretical and practical expression at the root of all the reforms implemented in our country.